Prosthetic Rehabilitation of Maxillectomy Cases - T. Samraj; G. T. Simon (Indian Journal of Plastic Surgery)
Methods of prosthetic rehabilitation from the time of surgery-fenestration, partial or hemi-maxillectomy and maxillectomy and literature review are presented. The various types of prosthetic appliances used for rehabilitation are classified and the advantages of each discussed.